LEGAL LIABILITY AND SOCIAL CONDUCT IN TRAFFIC ACCIDENTS: A CRITICAL ANALYSIS (CIPEEX, 2025)
This study examines traffic accidents through the lenses of criminal and civil law, highlighting their legal consequences and social implications in Brazil. The research employs a qualitative methodology, combining bibliographic review, document analysis, and interpretation of court decisions from the TJ-GO and STJ to clarify the practical application of laws. The analysis is grounded in sociological theories by Durkheim and Weber, which discuss social norms and rationality, as well as in concepts of criminal and civil liability present in Brazilian legislation, such as the Brazilian Traffic Code (CTB) and the Penal Code. The results indicate that collective awareness, strict enforcement of norms, and prompt assistance to victims are essential to mitigate accidents and their consequences. The conclusion emphasizes the need for effective public policies and educational measures to promote a culture of responsibility and reduce the high incidence of traffic fatalities, reinforcing the role of law in ensuring justice and social protection.
Keywords: Traffic accidents; Criminal liability; Civil liability; Social implications; Brazilian Traffic Code